UNJUK KERJA BOILER TIPE CFB PADA UNIT 2 PLTU SULUT-3 DENGAN METODE LANGSUNG - Rival Maulana; Frans Palobo Sappu; Benny Maluegha (JURNAL POROS TEKNIK MESIN UNSRAT, 2023)
Steam power plant is a steam powered power plant that rotate a turbine connected to generator to generate electricity. Steam produced by an equipment that called a boiler. Boilers produce steam by heating water with heat energy that generated by the combustion of fuel. This study was conducted to analyze how effective the boiler at PLTU Sulut-3 generating unit in absorbing heat energy from the fuel. The method used in this research is the calculation of efficiency with the direct method or the Input-Output method. Based on the results of efficiency calculations at 30MW power variations get an average efficiency of 78%, at 45 MW get an average efficiency of 80.09%, and at 55MW an average efficiency of 80.25%. From the results of the study, it was concluded that the greater the steam production in the boiler, the greater the efficiency. Keywords: boiler efficiency, direct method